Welcoming the neophytes / Badariah Bahruddin - Bahruddin, Badariah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Among the activities were a brief talk by the Rector and the Top Management of UiTM Perak Branch, an academic registration, an introduction to various departments and their functions, reli-gious talks, an introduction to students leaders (Majlis Perwakilan Pelajar or MPP) and an introduction to different college hostels. Students were assisted and monitored by the student facilita-tors throughout the orientation week.